The psychosocial impact of child domestic work: a study from India and the Philippines. Issue 9 (9th June 2012) - Hesketh, Therese M; Gamlin, Jennie; Ong, Michelle; Camacho, Agnes Zeneida V
Abstract : The aim of the study was to explore the effects of domestic employment on the well-being of child domestic workers (CDWs) in India and the Philippines. A questionnaire was administered to 700 CDWs and 700 school-attending controls in the two countries. In India, 36% of CDWs started work before age 12, 48% worked because of poverty or to repay loans, 46% worked >10 h per day, and 31% were physically punished by employers. Filipino CDWs were mainly migrants from rural areas, 47% were working to continue their studies and 87% were attending school, compared with 35% of Indians. In India, 67% of CDWs and 25% of controls scored in the lowest tertile (p<0.001) compared with 36% and 30%, respectively, in the Philippines (p=02). Key significant correlates of low psychosocial scores were non-attendance at school, long working hours, physical punishment, limited support networks and poor health. This study shows that it is not domestic work that is intrinsically harmful, but rather the circumstances and conditions of work, which could be improved through pragmatic regulatory measures.